Use of the D test method to detect inducible clindamycin resistance in coagulase negative staphylococci (CoNS) - Leandro Reus Rodrigues Perez; Juliana Caierão; Ana Lúcia Souza Antunes; Pedro Alves d'Azevedo (Brazilian Journal of Infectious Diseases)
According to the National Committee for Clinical Laboratory Standards (NCCLS, 2004), a method to evaluate the inducible clindamycin resistance in accordance with an approach of the disks of erythromycin and clindamycin - the D test - has been reported. We analyzed the performance of this method in 200 coagulase negative staphylococci (CoNS) strains obtained from blood cultures of hospitalized patients at a general hospital in Southern Brazil. Twenty-seven clinical isolates with suitable profile (erythromycin-resistant and clindamycin-susceptible) were evaluated for the D test realization. Thus, only 5 CoNS were D test positive. The D test method showed to be simple and an important technique in the detection of inducible clindamycin resistance.